Serum ferritin and C- reactive protein levels as indicators of severity of preeclampsia - Hanan Asaad Ismael; Abdulkareem Hamady Issa; Ban Hadi Hameed (Journal of the Pakistan Medical Association, 2024)
Objective: To assess the role of inflammatory markers ferritin and C- reactive protein as indicators of preeclampsia severity. Method: The case-control study was conducted at Al-Yarmouk Teaching Hospital, Baghdad, Iraq, from November 2021 to May 2022, and comprised pregnant women from the obstetrics ward and outpatient clinics aged 16-40 years having a viable singleton pregnancy and gestational age >32 weeks. They were divided into severe preeclampsia group A, non-severe preeclampsia group B and control group C. Serum ferritin and C-reactive protein levels were measured for all the subjects, and compared. Data was analysed using SPSS 26. Results: Of the 87 pregnant women, 27(31%) were in group A with mean age 29.76±7.53 years and mean gestational age 35.63±1.92 weeks, 29(33.33%) were in group B with mean age 26.83±6.30 years and mean gestational age 36.24±1.72 weeks, and 31(35.63%) were in group C with mean age 26.00±5.73 years and mean gestational age 36.52±1.61 weeks. Ferritin levels in patient groups were significantly higher than in the control group (p<0.05), but it was not significantly different between the patient groups (p>0.05). C-reactive protein levels in the patient groups were significantly higher than in the control group (p<0.05), and they were also significantly higher in group A than in group B (p<0.05). At a cut-off value >101.8 ferritin had sensitivity 92.59% but specificity 20.69%, whereas C- reactive protein at a cut-off value >17.1 had sensitivity 66.67% but specificity 75.86%. Conclusion: Serum C- reactive protein level was significantly associated with severity of preeclampsia with an acceptable grade of discriminative ability between severe preeclampsia and non-severe preeclampsia patients. Key Words: Eclampsia, Protein, Gestational, Ambulatory, Ferritins